DIFFUSION OF INNOVATION THEORY AND ADOPTION OF LIQUEFIED PETROLEUM GAS FOR COOKING (Journal of the Management Sciences, 2025)
This paper applied Rogers’ Diffusion of Innovation (DOI) Theory to adoption of liquefied petroleum gas (LPG). The target population includes the residents of four estates in Agege, Lagos State. A survey of households (N = 384) in the four estates in the Agege area of Lagos State, Nigeria was undertaken with a structured questionnaire. A multiple regression analysis was conducted to test the research hypotheses. The findings revealed that relative advantage (β = .288, T = 5.856, p
Keywords: Diffusion of Innovation Theory; Relative advantage; Compatibility; Complexity; Trialability; Observability